School adaptation of early Childhood Education to 8th grade (Research, Society and Development, 2021)
Among the major social challenges that to 21st century education it is possible to integrate and to socialize children with learning problems. The objective of the article was to identify the adaptation of children to the school context as an essential factor in the performance of the teaching-learning process. Research divided into two moments that formed the bibliography and research by means of interviews and analyzes. The bibliographic work is based on literature analyzes on the topic "School Adaptation" and seeks subsidies that raise questions on adaptation to schools, over the past two years, pois or subject matter been the object of studies related to educational area. For this study, support yourself in great educational researchers. Piaget (1959) and Froebel (1782), for some two authors investigated. The internet was another important source, as well as the School Regiment and the Pedagogical Political Plan (PPP) that provides indispensable help. Therefore, I understand that subjecting through “adaptive-mutilation”, through the combination of efforts between educators and families, it is possible to avoid adaptation problems, having in view that when these components (family and educators) They will unite, and together they will fulfill their role, perhaps there is no more reason for a rejecter child or school environment, because this will be, an true, an extension of their house.